University-Industry Cooperation: A Systematic Literature Review and Research Agenda - Mascaranhas, Carla (2019)
As university–industry cooperation is associated with the transfer of knowledge and technology, this collaboration is an extremely important field of study for the world’s economies that helps companies become more competitive. The present research, thus, sought to explore and analyse the literature related to university–industry cooperation, using a co-citation analysis. This study’s objectives were to (1) identify the main co-cited references and the groups (i.e. clusters) they form and (2) discuss the challenges this literature presented in the study of university–industry cooperation. The articles reviewed were obtained with a search of the ISI’s Web of Science and were submitted to a bibliometric analysis using VOSviewer software. This systematic literature review revealed that companies are increasingly focused on cooperation with universities. The results include four clusters, namely, (1) Absorption Capacity, Knowledge and Competitiveness in University–Industry Relations, (2) Impact of Knowledge Spill-overs on University–Industry Relations, (3) Strategic Alliances for Industry Innovation, and (4) University–Industry Cooperation. This study thus contributes to a greater and more detailed understanding of the production flow,scientific practices, and trends in this new and stimulating field of research.